Anticoagulant management of cancer-associated thrombosis and thrombocytopenia: a retrospective chart review - Umaima Abbas; Robin MacKenzie; Ushra Khan; Rija Fatima; Tzu-Fei Wang; Rong Luo; Caroline Hamm; Andrea Cervi (Research and Practice in Thrombosis and Haemostasis)
Background: Patients with cancer-associated thrombosis (CAT) are at an increased risk of recurrent thrombosis and bleeding, especially if there is treatment- or disease-related thrombocytopenia. While direct oral anticoagulants (DOACs) are used in the management of CAT, low molecular weight heparin (LMWH) continues to be recommended for CAT with thrombocytopenia. Objectives: This study aimed to identify the rates of recurrent venous thromboembolism (VTE) and bleeding in patients with CAT and thrombocytopenia treated with DOACs compared with LMWH. Methods: A retrospective review of patients with CAT and thrombocytopenia (platelet count <100,000/μL) was conducted. Primary outcomes included rates of recurrent VTE and major bleeding over 90 days. Results: Forty-two patients met the inclusion criteria; 20 (47.6%) had a solid organ malignancy while 22 (52.4%) had a hematologic malignancy. Within the first 7 days of VTE, 3 (7.1%) patients had a platelet count <25,000/μL, 9 (21.4%) had 25,000 to 50,000/μL, and 19 (45.2%) had 50,000 to 100,000/μL. Sixteen patients (38.1%) received a DOAC for initial treatment, while 19 (45.2%) received LMWH. Among patients treated with DOACs, there were no recurrent VTEs, 2 clinically relevant nonmajor bleeding events (12.5%) within the first 2 weeks, and 1 minor bleed (6.3%) in the second month, while those treated with LMWH had 1 recurrent VTE (5.3%) in the second month and 2 clinically relevant nonmajor bleeding events (10.5%) within the first 2 months. Conclusion: Rates of thrombosis and major bleeding were similar among thrombocytopenic patients with CAT treated with DOACs and LMWH, although differences in baseline patient characteristics can be confounders. Further prospective research on the optimal anticoagulant management of CAT with thrombocytopenia is needed.